Inovasi Pelayanan Publik Dinas Kependudukan Dan Catatan Sipil Kabupaten Batu Bara - Fika Nurtivanny; Nurhayati Nurhayati (Journal Economic Excellence Ibnu Sina, 2023)
Public services are government activities for the community. Public services try to create comfort for the community. This article discusses various public service innovations at the Population and Civil Registry Service. Updates on public services from the Batu Bara Regency Dukcapil Office, such as updates to Child Identity Card (KIA) Services, Moling E-KTP which is available in villages, children's playrooms, lataxi rooms. This research uses a qualitative method that collects data from the internet and describes how innovation develops from the development of public services at the Batu Bara Regency Population and Civil Registry Service. The aim of this research is to find out what public service innovations exist in the Batu Bara Regency Dukcapil Disdukcapil. The research results show that if technology develops in society, then public services must be accompanied by technical developments. With these various innovations, it is hoped that the Batu Bara Regency Population and Civil Registry Service can serve the people of Batu Bara well.